Solving inverse nodal problem with spectral parameter in boundary conditions - Akbarpoor, Sh.; Koyunbakan, H.; Dabbaghian, A. (Taylor & Francis Ltd, 2019)
In this study, the inverse Sturm-Liouville problem with spectral parameter in boundary conditions on a finite interval is considered. In fact, we use the nodes as input data and compute the approximation of solution of the inverse nodal Sturm-Liouville problem by the first kind Chebyshev polynomials and apply two methods Chebyshev wavelets and Chebyshev interpolation for solving inverse nodal Sturm-Liouville problem. Finally, the results are explained by presenting the numerical example.
Keywords: Sturm-Liouville equation; inverse problem; the nodes; Chebyshev wavelet; Chebyshev interpolation